(untitled) (Signifiances (Signifying), 2019)
In this paper we present the Saussurean conception of the duality of the linguistic sign. We thus aim at enlightening what is at stake in it, for linguistics and more generally for language sciences, in the widest sense of the word language, We first show that the Saussurean theorization of language (langue) constitutes an epistemological rupture (in Bachelard’s sense) in the history of linguistics, in that it theorizes for the first time the sound/meaning relationship, and that this rupture implies the distinction between language, (langue) and idiom. We then focus on delineating the Saussurean construction of the language space, which involves a plurality of objects, including the language, in the psychoanalytic sense of the word, as elaborated, after Freud and Lacan, by the psychoanalyst Alain Manier.